Evaluating volatile organic compounds from Chinese traditional handmade paper by SPME-GC/MS - Li Ding (SpringerOpen, 2021)
Abstract Once printed, books are always accompanied by the smells of volatile organic compounds (VOCs) which are continuously emitted not only by inks but also by papers themselves throughout their lives. Although the VOCs from papers may bring mild discomfort to readers, they are considered as very important factors that feature the degradation of papers and show potential applications in cultural relic appraisal. In this study, an analytical approach based on solid phase microextraction combined with gas chromatography-mass spectrometry (SPME-GC/MS) was proposed for the evaluation of volatile organic compounds (VOCs) emitted by Chinese traditional handmade papers. The VOCs evaluations and artificial aging processes were both applied to recent-made papers and naturally aged papers from a traditional Chinese calligraphy and painting scroll (collected by the National Museum of China). To be noticed, a large number of aliphatic acids, aldehydes, ketones, furan derivatives, benzene series and terpenoid substances indicated that the VOCs signals not only reveal the degradation of paper but also tentatively reflect the storage environment along hundreds of years ago. The semi-quantitative evaluation of markers indicated that the historical paper is under a serious degradation due to the high capacity it releases. Our results provided a path way to get the degradation information of ancient paintings as well as potential realistic applications such as the conservation of paper-based relics and the environmental protection in libraries and museums.